In the Wake of Trauma : Psychology and Philosophy for the Suffering Other - Goodman, David, 1980-; Becker, Brian W., 1980-; Severson, Eric R. (Book collections on Project MUSE., 2016)
"The essays range over a diverse landscape for inspiration--discussing thinkers such as Augustine, Ranciere, Foucault, Freud, Heidegger, Kristeva, and Lacan; literary works from Homer to Shakespeare to Joyce; case studies from clinical practice, film, even the book of Job & --all in order to identify new avenues for working through trauma's far-reaching effects, both for individuals and in its social and collective dimensions. Though these authors certainly do not speak with a singular voice, the volume is held together by an underlying 'ethical turn, ', a commitment to acknowledge the subjectivity of the victim. As the work demonstrates, this allows a kind of exploration not possible when adhering to a particular methodology or theory, thus avoiding the reductionism common to medical models for mental health."--Provided by publisher.